The Culture of Translation in Early Modern England and France, 1500-1660
XII, 231 p.
Keywords: This book explores modalities and cultural interventions of translation in the early modern period, focusing on the shared parameters of these two translation cultures. Translation emerges as a powerful tool for thinking about community and citizenship, literary tradition and the classical past, certitude and doubt, language and the imagination.